2018
DOI: 10.5539/jsd.v11n6p236
|View full text |Cite
|
Sign up to set email alerts
|

Why Goat Farming in Northern Communal Areas of Namibia Is not Commercialised: The Case of Ogongo Constituency

Abstract: In Namibia, goat products are not found in the formal markets include retail shops. This is despite several attempts by the government of Namibia to promote goat products in the formal sector. At household level however, goat meat is a delicacy. This study therefore seeks to provide possible reasons for the unavailability of goat products in Northern Namibia focussing on the supply side of the goat market. A structured survey questionnaire was employed among 75 goat farmers in Ogongo Constituency, Omusati Regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
1
3
1
Order By: Relevance
“…A higher percentage of married farmers sold goats when compared with single, widowed and cohabiting farmers. These results are in line with the studies by Togarepi et al (2018), who found that goat sales are more inclined to take place in married farmers than in single and in widowed farmers as this is attributed to collective decision-making and increased household needs for income by married farmers.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…A higher percentage of married farmers sold goats when compared with single, widowed and cohabiting farmers. These results are in line with the studies by Togarepi et al (2018), who found that goat sales are more inclined to take place in married farmers than in single and in widowed farmers as this is attributed to collective decision-making and increased household needs for income by married farmers.…”
Section: Resultssupporting
confidence: 92%
“…Elder sons in female-headed households may be the rightful owners of goats but may not have the enthusiasm of goat farming or see the need for selling. However, these results do not concur with the findings by Togarepi et al (2018) and Musemwa et al (2010), who found that the sale of cattle and goats was predominantly by pensioners and females who sold livestock to complement their income from remittances and government grants. This, however, corresponds with findings by Homann et al .…”
Section: Resultscontrasting
confidence: 89%
See 3 more Smart Citations